Kirant Folk Narratives: Exploring the Socio-Cultural Implications - Rai, Prakash (Sahayaatra सहयात्रा, 2023)
The paper analyzes how folk narratives in Kirant Rai shape the socio-cultural and ritual practices and values in day-to-day life. The core meanings of the narratives profoundly impact the formation and structure of socio-cultural beliefs and behaviors not only on people in a particular community but also on people from around the globe. Based chiefly on the two folk narratives— Hechchhakuppa and Sumdima and Paruhang, the paper analyzes the narrative texts under certain thematic issues such as the institutionalization of the human society, ritual performative, and representation by using functional, and socio-cultural theory by Dundes and Bascom respectively to spot the underlying impacts of the narratives on communities and people. The narrative texts which have been collected through fieldwork and transcription of oral narratives serve as primary data for the paper. When analyzing the texts, the folk narratives have been found to have greatly contributed to developing and transferring the belief system, ritual practice, and societal norms in the society.